A new high step-up soft switching converter for photovoltaic system. (16th December 2021) - Vesali, Mahmood; Delshad, Majid; Naeini, Ali Khajeh
In this paper, a new DC-DC boost converter with ZCS condition is presented. The ZCS condition of the proposed converter is established without adding any auxiliary switches and with minimum auxiliary elements, so the converter efficiency is high. The converter is controlled by pulse width modulation for which the design and implementation of the control circuit for the converter is very simple. The proposed converter has low current and voltage stress on the switch and the other advantage of the converter is high voltage gain due to existence of coupled inductors and voltage lifting in output, therefore the proposed converter is very suitable for photovoltaic systems. The experimental results verify the theoretical analysis and the converter efficiency at full load is approximately 96%.